Social interactions of Orang Asli preschoolers in Malaysia - Adam Assim, Mohd Ibrani Shahrimin; Yaccob, Yasmin; Mat Jusoh, Nurul Hidayu; Janis, Salina (Turkish Online Jounal of Qualitative Inquiry, 2021)
This study examined the patterns of socioculturally appropriate social interactions of Malaysia’s Orang Asli children in an educational computer environment. The socioculturally appropriate collaborative interaction were identified and classified into seven dominant categories. Factors facilitating and inhibiting the verbal and non-verbal interaction were examined and analyzed by using the sociocultural appropriateness framework. Rogoff’s Sociocultural Theory and the three foci of analyses: personal, interpersonal, and community or contextual planes were utilized in this study. A multi-method case study design was employed to identify the patterns of socioculutrally appropriate social interactions unique to the Malaysia’s Orang Asli preschool children in Selangor. 12 preschool children were observed and interviewed using a semi-structured questionnaire. Seven dominant interaction patterns related to socioculturally appropriate social interactions of Orang Asli preschool children were examined. Factors facilitating and inhibiting the social interactions were identified using the application of Rogoff’s three foci of analyses and series of semi-structured interviews with Malaysian preschool teachers and Orang Asli preschool children. Malaysian preschool educators will be informed to socioculutrally integrate the information and computer technology into their preschool classrooms and to promote positive prosocial interaction among Orang Asli children whilst engaged with the computer.